Multiple variants in 5q31.1 are associated with systemic lupus erythematosus susceptibility and subphenotypes in the Han Chinese population. (1st September 2017) - Wen, L.L.; Zhu, Z.W.; Yang, C.; Liu, L.; Zuo, X.B.; Morris, D.L.; Dou, J.F.; Ye, L.; Cheng, Y.Y.; Guo, H.M.; Huang, H.Q.; Lin, Y.; et al.
Summary: Background: A previous study provided evidence for a genetic association between PPP2CA on 5q31.1 and systemic lupus erythematosus (SLE) across multi‐ancestral cohorts, but failed to find significant evidence for an association in the Han Chinese population. Objectives: To explore the association between this locus and SLE using data from our previously published genome‐wide association study (GWAS). Methods: Single‐nucleotide polymorphisms (SNPs) rs7726414 and rs244689 (near TCF7 and PPP2CA in 5q31.1) were selected as candidate independent associations from a large‐scale study in a Han Chinese population consisting of 1047 cases and 1205 controls. Subsequently, 3509 cases and 8246 controls were genotyped in two further replication studies. We then investigated the SNPs' associations with SLE subphenotypes and gene expression in peripheral blood mononuclear cells. Results: Highly significant associations with SLE in the Han Chinese population were detected for SNPs rs7726414 and rs244689 by combining the genotype data from our previous GWAS and two independent replication cohorts. Further conditional analyses indicated that these two SNPs contribute to disease susceptibility independently. A significant association with SLE, age at diagnosis < 20 years, was found for rs7726414 ( P = 0·001). The expression levels of TCF7 and PPP2CA messenger RNA in patients with SLE were significantly decreased compared with those in healthy controls. Conclusions: This study found evidence for multiple associations with SLE in 5q31.1 at genome‐wide levels of significance for the first time in a Han Chinese population, in a combined genotype dataset. These findings suggest that variants in the 5q31.1 locus not only provide novel insights into the genetic architecture of SLE, but also contribute to the complex subphenotypes of SLE.